Transcription factors: key regulatory targets of vascular smooth muscle cell in atherosclerosis - Yu Jiang; Hai-Yan Qian (BMC, 2023)
Abstract Atherosclerosis (AS), leading to gradual occlusion of the arterial lumen, refers to the accumulation of lipids and inflammatory debris in the arterial wall. Despite therapeutic advances over past decades including intervention or surgery, atherosclerosis is still the most common cause of cardiovascular diseases and the main mechanism of death and disability worldwide. Vascular smooth muscle cells (VSMCs) play an imperative role in the occurrence of atherosclerosis and throughout the whole stages. In the past, there was a lack of comprehensive understanding of VSMCs, but the development of identification technology, including in vivo single-cell sequencing technology and lineage tracing with the CreERT2-loxP system, suggests that VSMCs have remarkable plasticity and reevaluates well-established concepts about the contribution of VSMCs. Transcription factors, a kind of protein molecule that specifically recognizes and binds DNA upstream promoter regions or distal enhancer DNA elements, play a key role in the transcription initiation of the coding genes and are necessary for RNA polymerase to bind gene promoters. In this review, we highlight that, except for environmental factors, VSMC genes are transcriptionally regulated through complex interactions of multiple conserved cis-regulatory elements and transcription factors. In addition, through a series of transcription-related regulatory processes, VSMCs could undergo phenotypic transformation, proliferation, migration, calcification and apoptosis. Finally, enhancing or inhibiting transcription factors can regulate the development of atherosclerotic lesions, and the downstream molecular mechanism of transcriptional regulation has also been widely studied.